Eye-tracking based Methodological framework for optimal distribution of online advertisement locations - Michaelidou, Eleni; Zaphiris, Panayiotis; Christoforou, Christoforos (My University, 2013)
Similar with the rest of the world, Internet in Cyprus is now used as a mean of low cost targeted advertising. With more than 30 thousand Cypriot Websites and with Cyprus Web usage rising to 50,2% in 2010, online advertising is now the upcoming trend in advertising expenses in Cyprus. The increase in the number of commercial Cypriot Website, and consequently the increase of available online advertising spots raise the question: Which advertising locations has to be chosen by an agent in order to optimize the effectiveness and maximize the visibility of an online campaign? There are currently around 10 thousand available advertising positions and types of advertisements. Currently, online advertisement placement is highly subjective and is performed by an advertising agent who typically chooses the position based of his personal experience, generic statistical data and on the motto that “the higher the position of the ad on the page, the more effective” The project’s main aim is to implement an evaluation methodology service for the identification of the best locations on Cypriot web space based on eye tracking studies. This will first consist of the state-of-the-art analysis in existing patterns of advertisement placement on websites. Then user data will be collected with the use of eye tracking technologies in order to understand how users look at Web advertising and how effective each location is. A methodological framework will be then developed based on a prediction model for the optimization of the online advertising locations. Factors such as the advertising budget, social status, and Web use will be some of the many to be considered. This innovative project would benefit anyone who want to advertise on the Web since it will be based on factual research with an eye tracker and volunteers from Cyprus. Advertising will now be based on facts, not just speculative statistics. The outcome of this project will help the future of advertisement on the Web.
Keywords: Online advertisement; Optimal distribution